Optimization of production planning for food and beverage MSMEs: case in the covid-19 pandemic - Vita Sarasi; Nugroho Djati Satmoko; Vivian Winita (Operations Excellence: Journal of Applied Industrial Engineering, 2023)
Micro, Small, and Medium Enterprises (MSMEs) in the food and beverage sector is one of the sectors negatively affected by the COVID-19 outbreak, even though this sector is one of the largest contributors to the Gross Domestic Product of the non-oil and gas industry in Indonesia. This study intends to provide an overview of solutions in the form of case studies on the Mahkota Caman MSME in Bekasi, Indonesia, which experienced a decline in sales during the pandemic, resulting in overstock and damage to non-durable raw materials. As a result, it leads to an increase in inventory costs and even a loss of sales. The solution offered by this study is an optimization of production planning, namely determining what products and how many of these products should be produced in a certain period. The method used is goal programming, both with and without priority, so that Mahkota Caman can meet consumer demands, and minimize production costs, while minimizing the purchase of raw materials. The results of this study indicate that the optimal optimization method used by Mahkota Caman is goal programming with priority because it provides a more efficient solution to production costs and the purchase of raw materials. Based on the results of this study, it is recommended that optimization methods be used by MSMEs in the food and beverage sector during a pandemic, and to avoid using only feeling in production planning.